Continuities and changes in Maya archaeology : perspectives at the millennium - Golden, Charles W., 1972-; Borgstede, Greg, 1972- (Routledge, 2004)
Presents the current state of of Maya archaeology by focusing on the history of the field for the past hundred years, present day research, and forward looking prescription for the direction of the.